2006
DOI: 10.1590/s0074-02762006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Triatoma venosa (Hemiptera: Reduviidae): molecular and morphometric evidence

Abstract: Triatoma venosa presents a restricted geographical distribution in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
0
6
0
2
Order By: Relevance
“…In our study, 17% of T. venosa collected were nymphs, and 71.4% were collected in intradomiciliary areas. Considering that previously ecoepidemiological studies in Boavita (Boyaca) showed high mobility of species between peridomicile and intradomiciliary environments [45], the results in the current study could be a consequence of T. venosa mobility in the peridomicile area or a result of a peculiar domiciliation of this triatomine species in this department [9,17]. Therefore, we suggest that both scenarios should be explored.…”
Section: Discussionmentioning
confidence: 74%
“…In our study, 17% of T. venosa collected were nymphs, and 71.4% were collected in intradomiciliary areas. Considering that previously ecoepidemiological studies in Boavita (Boyaca) showed high mobility of species between peridomicile and intradomiciliary environments [45], the results in the current study could be a consequence of T. venosa mobility in the peridomicile area or a result of a peculiar domiciliation of this triatomine species in this department [9,17]. Therefore, we suggest that both scenarios should be explored.…”
Section: Discussionmentioning
confidence: 74%
“…Because the statistical analyses of genetic variability expressed by morphological characters are a good measure of population differentiation (Patterson et al, 2001), morphometrics is an efficient alternative method for taxonomic studies of Triatominae (Dujardin et al, 1999;Matias et al, 2001;Jaramillo et al, 2002;Villegas et al, 2002;Gumiel et al, 2003, Lehmann et al, 2005Vargas et al, 2006;Feliciangeli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Todas estas particularidades del hábitat, parecen afectar de un modo específico las características morfofisiológicas de T. infestans resultando en cambios que serían de utilidad para la identificación de insectos recolonizantes o con diferentes capacidades dispersivas (Schachter-Broide et al, 2004;Abrahan et al, 2008;Hernández et al, 2011;Hernández et al, 2013). Diversas son las investigaciones que dan cuenta del uso la técnica de morfometría geométrica y fenotipos antenales en triatominos para análisis de dispersantes (Dumonteil et al, 2007), estructura poblacional (Vargas et al, 2006;Schachter-Broide et al, 2004;Hernández et al, 2011;Gaspe et al, 2012) características fenéticas compatibles con vuelo, entre otros (Hernández et al, 2015;Hernández et al, 2020). El análisis de la estructuración espacial poblacional permite determinar la continuidad que puede existir en la distribución geográfica de las poblaciones de una especie, mediante la caracterización de sus individuos y la comparación de variables relacionadas al fenotipo, al genotipo, o ambas (Dujardin et al, 2002).…”
Section: Introductionunclassified